Motion Synthesis for Sports Using Unobtrusive Lightweight Body‐Worn and Environment Sensing. (27th May 2013) - Kelly, P.; Conaire, C. Ó; O'Connor, N. E.; Hodgins, J.
<x xml:space="preserve">Abstract</x> The ability to accurately achieve performance capture of athlete motion during competitive play in near real‐time promises to revolutionise not only broadcast sports graphics visualisation and commentary, but also potentially performance analysis, sports medicine, fantasy sports and wagering. In this paper, we present a highly portable, non‐intrusive approach for synthesising human athlete motion in competitive game‐play with lightweight instrumentation of both the athlete and field of play. Our data‐driven puppetry technique relies on a pre‐captured database of short segments of motion capture data to construct a motion graph augmented with interpolated motions and speed variations. An athlete's performed motion is synthesised by finding a related action sequence through the motion graph using a sparse set of measurements from the performance, acquired from both worn inertial and global location sensors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>